PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMEN (TGT) TERHADAP HASIL BELAJAR PADA MATERI LINGKARAN KELAS VI SISWA MI DARUSSALAM PACET: THE INFLUENCE OF COOPERATIVE LEARNING MODELS TEAMS GAMES TOURNAMENT (TGT) ON LEARNING OUTCOMES ON CLASS VI CIRCLE MATERIAL FOR MI DARUSSALAM PACET STUDENTS - Muhammad Akmal Kosnadi; Yhasinta Agustyarini (PT. Intelek Cendikiawan Nusantara, 2024)
Abstract Education in Indonesia is currently not said to be good, especially in mathematics education. This is in accordance with the results of PISA 2022 which explains that Indonesia is ranked 64 participating countries in the category of mathematical ability, as well as students in MI Darussalam Pacet. Based on the results of the Daily Test as many as 58% of grade VI students do not meet the minimum completeness criteria score, students tend to think that mathematics subjects are difficult to understand and boring. The use of methods that can generate enthusiasm for learning is indeed important, such as the TGT type cooperative learning method that combines games and tournaments in learning. The purpose of this study is to determine the implementation and influence of the Teams Games Tournament (TGT) type cooperative learning model on the learning outcomes of grade VI students in the mathematics subject of Circle material at MI Darussalam Pacet. Using the type of research One group pre-test post-test design. In the implementation of the Teamss game tourament (TGT) type cooperative learning model, data analysis obtained that the average learning outcomes of experimental class students is 74.9, so the average score of experimental class students can improve learning outcomes. Based on the output, it is known that the value of the correlation coefficient (correlations) is 0.790 with a signification value (Sig.) of 0.000. Because of the value of sig. 0.000 > a probability of 0.05, then it can be said that there is a relationship between the Pre-Test variable and the Post-Test variable. so it can be concluded that the Teams Games Tournament Model can improve student learning outcomes. Keywords:Cooperative, Teams Games Tournament (TGT), Learning Outcomes